Finding safe harbour: supporting the integration of refugee youth - Pelley, Emily (McGill-Queen's refugee and forced migration studies, 2022)
An Introduction to this Research -- Global Displacement and Youth -- Assessing Integration Support in Canada -- Services and Supports for Refugee Youth in Halifax, Nova Scotia: Findings and Reflections -- Supporting the Resilience and Integration of Refugee Youth: A Community Resilience Perspective -- Implications for Policy and Practice in Halifax, Nova Scotia Notes.